Renewable process heat from solar thermal and photovoltaics: The development and application of a universal methodology to determine the more economical technology. (15th February 2018) - Meyers, Steven; Schmitt, Bastian; Vajen, Klaus
Highlights: Solar thermal and photovoltaics for process heat generation were assessed. A methodology economically comparing solar thermal and photovoltaics was developed. Solar thermal is less expensive in most regions at current investment costs. Photovoltaics have advantages at higher process temperatures in cloudier regions. Solar thermal remains a preferred renewable heat solution under 250 €/m 2 turn-key. Abstract: Solar energy is an important measure to reduce fossil fuel use and carbon emissions from the energy supply in industries requiring heat below 150 °C. A robust methodology was developed to compare two solar conversion technologies (solar thermal and photovoltaics via resistance heating) to determine which provided lower cost heat, highly flexible for various plant sizes, investments, currencies, locations, and process temperatures. At current PV investments, solar thermal plants must be installed turn-key below 400 €/m 2 ap in northern European climates and 500 €/m 2 ap in southern to remain economically competitive. Photovoltaic heat is already the lower cost heat provider for many applications in northern latitudes above 100 °C. In future PV cost scenarios, solar thermal must reduce investments below 250 €/m 2 ap to remain competitive in Europe and 400 €/m 2 ap in higher solar resource regions. When opportunity costs are considered, photovoltaics are better utilized to offset local electrical, not thermal, demand. Despite this fact, future efforts must be given to solar thermal cost reduction in order to remain competitive against all other renewable heat producers.